Formulation of Priority Strategy for Implementing Performance Management in F&B MSMEs Using SWOT and QSPM Approaches - Zelinka Natalia Angelina; M. Syamsul Maarif; Yudha Heryawan Asnawi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The food and beverage sector competition demands efficiency and digital readiness amid managerial and digital constraints. This study aims to determine priority strategies to improve the performance of MSMEs in the food and beverage sector, with a case study. The methods employed in this study use a mixed-method approach, combining qualitative analysis and quantitative strategic tools, including business model canvas for initial business mapping, internal factor evaluation matrix, external factor evaluation matrix, internal-external matrix, SWOT analysis, and quantitative strategic planning matrix. The results indicate that the F&B MSME is positioned in cell V (hold and maintain) based on the IE matrix. The SWOT analysis generates several alternative strategies, which are further evaluated using a quantitative strategic planning matrix to determine priority strategies. The main selected strategy is WO2, which focuses on improving internal management systems, including expanding cashier access and developing more structured operational standard operating procedures supported by the potential for increasing online-based sales volume, with the highest Total Attractiveness Score (TAS) of 4.18. The next strategies are WO1 (TAS 3.31) and WT2 (TAS 3.01), which emphasize improving human resource competencies and enhancing digital promotion activities.